Detection of myocardial infarction by dual-source coronary computed tomography angiography using quantitated myocardial scintigraphy as the reference standard. Issue 17 (5th February 2009) - Rubinshtein, R; Miller, T D; Williamson, E E; Kirsch, J; Gibbons, R J; Primak, A N; McCollough, C H; Araoz, P A
Abstract : Background: Dual-source coronary computed tomography angiography (DS-CTA) has the potential to assess both coronary anatomy and myocardial perfusion. We studied the ability of DS-CTA to detect myocardial infarction (MI) compared to a reference standard of technetium Tc 99 m sestamibi single photon emission computed tomography (SPECT). Methods: 122 patients with suspected or known coronary artery disease (age 60 (SD 11) years, 36% females) were evaluated by both DS-CTA and SPECT. SPECT-MI size was quantitated using a threshold value of 60% of peak counts on the resting images. MI on DS-CTA was defined as transmural or subendocardial hypoenhancement (<50% of surrounding myocardium), which persisted in both diastolic and systolic reconstructions and was concordant with a coronary artery territory. The performance of DS-CTA to detect SPECT-MI was determined in a blinded, vessel-based analysis. Results: 366 vessel territories were analysed (122 patients ×3). SPECT revealed 20 vessel territories with MI (involving 17 patients). 15/20 (75%) of these vessel territories were also detected by DS-CTA. An additional seven MIs were detected by DS CTA only (considered as false positive). Thus, the sensitivity of DS-CTA for detection of SPECT-MI was 75% (95% CI 56% to 94%), specificity 98% (97% to 100%), positive predictive value 68% (49% to 88%) and negative predictive value 99% (97% to 100%). DS-CTA detected 10/11 (91%) larger MIs (involving >5% of left ventricular (LV) mass by SPECT). For the 15 concordant MIs (in both SPECT and DS-CTA) the mean difference in MI size between modalities was 0.5% (4.6%) of LV mass (95% CI −8.6% to 9.5%). Conclusions: DS-CTA myocardial perfusion imaging showed moderate sensitivity and positive predictive value but high specificity and negative predictive value for detection of SPECT-MI. Most large infarcts (>5% of LV mass) were detected by DS-CTA. When MI was detected by both modalities, there was a good correlation between infarct sizes quantitated by DS-CTA vs SPECT.